Spectrum of thoracic systemic venous abnormalities using multidetector computed tomography - Samar Shehata; Ghada Abdulmonaem; Aya Gamal; Mostafa Assy (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Anomalies of the thoracic systemic venous return vary widely and range from those with completely normal physiology to severe right to left shunting thus requiring surgical correction. The aim of the study is to enhance the awareness of multidetector computed tomography (MDCT) role in evaluation of systemic venous abnormalities, and be familiar with the imaging characteristics of even the extremely rare abnormalities. Results Among 270 examined patients, 15.19% had systemic venous abnormalities. Inferior vena cava (IVC) congenital anomalies accounted for (24.4%) of the detected abnormalities (prevalence: 3.7% among the studied population) where IVC interruption with azygos continuation was the most common detected IVC abnormality accounting for 17.7% of the detected abnormalities (prevalence: 2.6%), while IVC thrombosis accounted for 21.9% (prevalence: 3.3%). Persistent left sided superior vena cava (SVC) accounted for 14.6% of the detected abnormalities (prevalence: 2.2%), while SVC syndrome represented 19.5% (prevalence: 2.9%) and SVC aneurysm represented 2.4% (prevalence: 0.37%). Retroaortic brachiocephalic vein (BCV) and BCV thrombosis accounted for 7.3% each (prevalence: 1.1). Finally, persistent levo-atrial cardinal vein represented 2.4% of the detected abnormalities (prevalence: 0.37%). Conclusions MDCT is a non-invasive modality that can provide detailed information about the systemic thoracic veins before surgical or interventional procedures, especially in patients with congenital anomalies.